2013
DOI: 10.1136/amiajnl-2012-001414
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an electronic medication management system on hospital doctors' and nurses' work: a controlled pre–post, time and motion study

Abstract: ObjectiveTo quantify and compare the time doctors and nurses spent on direct patient care, medication-related tasks, and interactions before and after electronic medication management system (eMMS) introduction.MethodsControlled pre–post, time and motion study of 129 doctors and nurses for 633.2 h on four wards in a 400-bed hospital in Sydney, Australia. We measured changes in proportions of time on tasks and interactions by period, intervention/control group, and profession.ResultseMMS was associated with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 41 publications
1
82
3
Order By: Relevance
“…Our focus on scheduled drug rounds, rather than the entire working day, limits comparison with some previous studies [12]. Our findings also differ to a previous study that reported a reduction in drug administration round duration [3].…”
Section: Comparison With Previous Studiescontrasting
confidence: 99%
See 2 more Smart Citations
“…Our focus on scheduled drug rounds, rather than the entire working day, limits comparison with some previous studies [12]. Our findings also differ to a previous study that reported a reduction in drug administration round duration [3].…”
Section: Comparison With Previous Studiescontrasting
confidence: 99%
“…Within the UK, Barber et al [9] explored nurses' attitudes towards ePMA implementation, noting reluctance before implementation which changed to acceptance afterwards. Other international studies [10][11][12][13] suggest that ePMA may have a negative effect on communication between nurses and doctors [10] and impede work patterns [11]. Little is known about the effect on nurses' work during drug rounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend raises questions if the amount of time pharmacists spend doing clinical activities could decrease with the depth of CPOE implementation. A similar time-and-motion study was published by Westbrook et al [24] in 2013 that measured how introduction of an electronic medication management system (eMMS) affected the amount of time doctors and nurses spent on direct patient care and medication tasks, and it was concluded that the introduction of eMMS did not redistribute time spent on medication tasks or direct patient care.…”
Section: A Particular Facet Of the Results Is That While Time Spent Onmentioning
confidence: 82%
“…Moderate ease of use (Weinhara et al, 2009;Whittaker et al, 2009). Observed increased time spent on direct patient care and nursing documentation, and decreased time spent on administrative tasks (Banner & Olney, 2009) in contrast to no significant change in time spent on patient care (Westbrook et al, 2013).…”
Section: Themes Summary Of Findings Usability Ease Of Use / Efficiencymentioning
confidence: 99%